The Responsive Feeding Behavior and Stunting Incident on Toddlers - Ulfatul Latifah; Ratih Sakti Prastiwi; Umi Baroroh (JURNAL KEBIDANAN, 2020)
Stunting is a condition where the children have short stature caused by chronic malnutrition. Stunting could interfere with physical development and affects low intelligence levels. Based on basic health research data in 2019,the stunting rate in Indonesia reached 27.6%. WHOs' The WHO targeted stunting rate should be under 20%. In 2019, Tegal city had 830 children aged 0-5 years with stunting,and for the Margadana regency,there were 80 toddlers. This study aimed to determine the correlation of responsive feeding behavior and the incidence of stunting. This study was an observational study with a case-control design,with a ratio of 1:1. The population of this research was mothers who have toddlers aged 6-36 months. The sample was 28 respondents divided into two groups. Subjects who entered the stunting group had a PB/U z-score-2 SD,and subjects in the normal group had a PB/U-2SDz-score to 2SD. Data collection through interviews was to assess Knowledge,Attitudes,and Responsive Feeding Behavior and analyze the correlation with stunting and assessing the amount of risk for each variable. The data analyzed using Chi-Square on the study results show a relationship between knowledge,attitudes,and responsive feeding behavior with stunting. Based on the risk factor for lack of knowledge,the risk is 6.2 times greater for children experiencing stunting and unfavorable attitudes, 6.6 times greater risk for stunting children. At the same time, good behavior has a lower risk of 0.15 children experiencing stunting. It is hoped that toddlers' mothers can improve responsive feeding knowledge,attitudes,and behaviors so that toddlers' nutritional needs will be even better.